2022
DOI: 10.3390/microorganisms10020274
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Phenotypes, Cell Division, and Gene Expression of Escherichia coli under High Concentration of Sodium Sulfate

Abstract: Sodium and sulfate ions are among the suggested abundant ions on Europa, a moon of Jupiter. In order to investigate the potential habitability of Europa, we study the effects of sodium sulfate (Na2SO4) on a non-halophilic bacterium by subjecting Escherichia coli (E. coli) to a wide range of Na2SO4 concentrations (0–1.0 m). We discover that, as the concentration of sodium sulfate increases, the biomass doubling time increases and the cell growth is completely inhibited at 1.0 m Na2SO4. Furthermore, we find that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 98 publications
0
9
0
Order By: Relevance
“…It was observed that the growth inhibition (%) of Escherichia coli decreased proportionally with the decrease of the tested solution’s concentration. This fact could be associated with the expression of different genes involved in, e.g., sulfate transport as an adaptation mechanism [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that the growth inhibition (%) of Escherichia coli decreased proportionally with the decrease of the tested solution’s concentration. This fact could be associated with the expression of different genes involved in, e.g., sulfate transport as an adaptation mechanism [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Europa, a moon of Jupiter, is a prime candidate due to the presence of liquid water ocean running 100-200 km deep, with hydrostatic pressure reaching 130-260 MPa. [19][20][21] Therefore, the use of GFP as a cellular probe requires a systematic study of the effect of these environmental conditions on the properties of GFP.…”
Section: Introductionmentioning
confidence: 99%
“…The acceleration of the first step could be caused by protecting cells against oxidative stress [21] and/or providing a relatively rapid dioxygen regeneration from the decomposition of H 2 O 2 . The significant decrease in vanillin production could be related to the oxidation of sodium sulfite, which can inhibit the activity of NOV1 F , an iron‐containing dioxygenase [22,23] . Following this hypothesis, the biological alternative, 1 mg of catalase (corresponding to the decomposition of 2–5 mM H 2 O 2 per minute, at pH 7 and 25 °C), indeed improved the yield of vanillin, confirming the toxicity of excess hydrogen peroxide accumulating in the reaction.…”
Section: Resultsmentioning
confidence: 80%
“…The significant decrease in vanillin production could be related to the oxidation of sodium sulfite, which can inhibit the activity of NOV1 F , an ironcontaining dioxygenase. [22,23] Following this hypothesis, the biological alternative, 1 mg of catalase (corresponding to the decomposition of 2-5 mM H 2 O 2 per minute, at pH 7 and 25 °C), indeed improved the yield of vanillin, confirming the toxicity of excess hydrogen Regardless of the ratio between the two cell types, vanillin production did not exceed 10%. Sodium sulfite and catalase were supplied to quench the excess of H 2 O 2 .…”
Section: Cascade Conversions: Simultaneous Vs Stepwise Addition Of Wh...mentioning
confidence: 79%